2017
DOI: 10.1007/s40333-017-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of soil seed banks at different geomorphic positions within the longitudinal sand dunes of the Gurbantunggut Desert, China

Abstract: Understanding the characteristics of soil seed banks in sand dunes is crucial to stabilize the dune systems and maintain the plant populations in deserts. In this study, we conducted a survey investigation in the field and a seed germination experiment in the laboratory to explore the characteristics of soil seed banks at various geomorphic positions of longitudinal sand dunes in the Gurbantunggut Desert, China. Totally, 17 plant species belonging to 17 genera and 9 families were identified in soil seed banks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The overall number of families and species in the SSB were far lower than that of aboveground flora in the study areas. In the present study, the number of species in the SSB was comparable with a research report by Fengqin et al (2017) but their findings show that less number of species and families in the aboveground flora were recorded than present results. In our study, higher frequent families were recorded in SSB of non-invaded woodlands than habitats under Prosopis canopies such as Prosopis thicket and Prosopis with native species stands.…”
Section: Effects Of Prosopis Invasion On Species Compositionsupporting
confidence: 86%
See 1 more Smart Citation
“…The overall number of families and species in the SSB were far lower than that of aboveground flora in the study areas. In the present study, the number of species in the SSB was comparable with a research report by Fengqin et al (2017) but their findings show that less number of species and families in the aboveground flora were recorded than present results. In our study, higher frequent families were recorded in SSB of non-invaded woodlands than habitats under Prosopis canopies such as Prosopis thicket and Prosopis with native species stands.…”
Section: Effects Of Prosopis Invasion On Species Compositionsupporting
confidence: 86%
“…The highest H′ and E′ might also be due to the environmental suitability such as high moisture and soil fertility favored the above vegetation flora in east and northwest facings (Chapman and McEwan 2018). Geomorphic position, aspect, and micro-slope affect species richness and soil seed banks primarily through modulating soil water availability and soil erosion susceptibility might also be the cause for the decline in the either of the slope position except for the east and northwest facings (Fengqin et al 2017).…”
Section: Status Of Soil Seed Densitymentioning
confidence: 99%
“…In arid and semi-arid areas, vegetation patterns and pedogenesis are highly affected by extreme climate conditions, and also by the topography (Jia et al, 2017;Cerdà et al, 2018). Flat areas, such as alluvial fans, valleys or lagoons, that are highly exposed to high peaks of insolation, register high average temperatures with prolonged dry seasons that enhance high evapotranspiration rates (Li et al, 2016), the difficulties of organic matter consolidation (Wang et al, 2016), the generation of soil crusts (Singer and Shainberg, 2004) and the reduction of available water for the plants (Amare et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies indicate higher seed abundance in the most superficial soil layers (Baider et al, 2001;Bossuyt et al, 2002;Costa & Araújo, 2003;Luzuriaga et al, 2005;Wang et al, 2009;Santos et al, 2010;Silva et al, 2013;Savadogo et al 2017), which is favored by constant seed replacement, which determines the maintenance of the species in the plant community (Bossuyt et al, 2002). However, few studies have shown variations in richness (Korb et al 2005;Wang et al, 2009;Jia et al, 2017), mainly due to the difficulty of species identification. According to Jia et al (2017), environmental factors such as soil characteristics, topography, climate and vegetation distribution play an important role in the formation of the soil seed bank.…”
Section: /9mentioning
confidence: 99%
“…However, few studies have shown variations in richness (Korb et al 2005;Wang et al, 2009;Jia et al, 2017), mainly due to the difficulty of species identification. According to Jia et al (2017), environmental factors such as soil characteristics, topography, climate and vegetation distribution play an important role in the formation of the soil seed bank.…”
Section: /9mentioning
confidence: 99%